Digital De-Citizenship: The Rise of the Digital Denizen in Bahrain - Marc Owen Jones (14068734) (2020)
Revolutions seldom involve more than one percent of the population. However, in Bahrain, a small island nation with a population of around 570,000, twenty percent of the population took to the streets in February 2011 to demand greater democratic reform, making it “proportionally one of the greatest shows of ‘people power’ in modern history.” The regime's response was disproportionally brutal. Saudi-dominated troops from the Gulf Cooperation Council Peninsula Shield Force were “invited to” or “invaded” Bahrain, depending on who is telling the story. Under cover of the Saudi military, Bahrain's security forces killed dozens of civilians, torturing, maiming, and raping many others. The arsenal of repressive techniques was exhaustive. Belonging also was used as a tool of repression, with many being stripped of their Bahraini citizenship on spurious, terror-related charges.  Other information Published in: International Journal of Middle East Studies License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1017/S0020743820001038